Pengaruh Kualitas Pelayanan terhadap Kepuasan dan Loyalitas Anggota Koperasi Sangosay Cabang Ruteng Kabupaten Manggarai Provinsi Nusa Tenggara Timur - DOSOM, MARIA IRMAYANTI; ANGGRENI, I G A A LIES; AGUNG, I DEWA GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.10, No.2, Desember 2021, 2021)
The  Effect of Service Quality on Satisfaction and Loyalty of Members of the Sangosay Cooperative, Ruteng   branch, Manggarai Regency, East Nusa Tenggara Province The a cooperative is a business entity that is formed together with the principle of kinship. One type of cooperative that is of interest to people in Indonesia is the Savings and Loans Cooperative or credit cooperative. One of the savings and loan cooperatives in Indonesia is the Sangosay Cooperative, Ruteng branch, Manggarai Regency, East Nusa Tenggara Province. Service quality is an important thing that must be considered in advancing cooperatives. This study aims to analyze the effect of service quality on satisfaction and loyalty of members of the Sangosay Cooperative, Ruteng branch, Manggarai Regency, East Nusa Tenggara Province. Respondents in this study were members of the Sangosay cooperative, Ruteng branch who visited the Sangosay cooperative. The number of samples is 99 respondents obtained based on the accidental sampling method. The model was designed based on the Structural Equation Modeling (SEM) approach based on Smart PLS version 3.0 which was analyzed using a computer program. The results showed that the service quality faktor significantly affected the satisfaction of the members of the Sangosay cooperative, Ruteng branch (p = 0.000), the service quality faktor has a significant effect on the loyalty of members of the Sangosay cooperative, Ruteng branch (p = 0.000) and the satisfaction faktor has a significant effect on loyalty of members of the Sangosay cooperative, Ruteng branch (p = 0.000). Based on the research results, it is hoped that the Sangosay cooperative, Ruteng branch, will be able to maintain and improve the quality of service so that members feel satisfied and become loyal to the cooperative.